Investigations of key issues on the reproducibility of high-Tc superconductivity emerging from compressed La3Ni2O7 - Yazhou Zhou; Jing Guo; Shu Cai; Hualei Sun; Chengyu Li; Jinyu Zhao; Pengyu Wang; Jinyu Han; Xintian Chen; Yongjin Chen; Qi Wu; Yang Ding; et al. (Matter and Radiation at Extremes)
Signatures of superconductivity near 80 K have recently been discovered in single crystals of La3Ni2O7 under pressure, which makes it a new candidate for high-temperature superconductors dominated by 3d transition elements, following the cuprate and iron-pnictide superconductors. However, there are several critical questions that have been perplexing the scientific community: (1) What factors contribute to the inconsistent reproducibility of the experimental results? (2) What is the fundamental nature of pressure-induced superconductivity: bulk or nonbulk (filamentary-like)? (3) Where is the superconducting phase located within the sample if it is filamentary-like? (4) Is the oxygen content important for the development and stabilization of superconductivity? In this study, we employ comprehensive high-pressure techniques to address these questions. Through our modulated ac susceptibility measurements, we are the first to find that the superconductivity in this nickelate is filamentary-like. Our scanning transmission electron microscopy investigations suggest that the filamentary-like superconductivity most likely emerges at the interface between La3Ni2O7 and La4Ni3O10 phases. By tuning the oxygen content of polycrystalline La3Ni2O7, we also find that it plays vital role in the development and stabilization of superconductivity in this material. The upper and lower bounds on the oxygen content are 7.35 and 6.89, respectively. Our results provide not only new insights into the puzzling issues regarding this material, but also significant information that will enable a better understanding of its superconductivity.